Creativity in Philosophy: A Multifaceted Approach to Education with Mulla Sadra's Thinking - Afzal Sadat Hosseini (SYAMIL: Journal of Islamic Education, 2023)
Solving today's problems and preparing for future uncertainties requires creativity. Creativity has been placed as one of the main axes of educational reforms in many advanced educational systems of the world. The current research, which is of a fundamental type and descriptive-analytical method, seeks to explain the solid philosophical foundations for the multifaceted theory of educational creativity presented by the author of this article based on Mulla Sadra. Mulla Sadra is one of the great Muslim philosophers. According to the findings of the present research, the theory of multifaceted educational creativity, which has environmental-social, emotional-cognitive, intellectual, educational-teaching and physical dimensions for creativity, can be based on the anthropological philosophy of Mulla Sadra, which attributes "becoming" to human nature. In this article, several practical suggestions for teachers based on the theory of multifaceted educational creativity have been presented so that teachers can take more effective steps to foster students' creativity. Also, suggestions for future researches have been provided.